Efficacy of pegylated interferon α-2b plus entecavir therapy and predictors of treatment success in children with chronic hepatitis B - Huang, Liang; Zhang, Hong; Kang, Xintong; Chen, Zhu; Wang, Lin; Zeng, Yilan (Frontiers in Immunology, 2023)
Interferon therapy, used in the treatment of chronic hepatitis B(CHB), is one of the means by which patients can achieve functional cure. Pegylated interferon is currently used in treatment for CHB.There are two main types of pegylated interferon: α-2b and α-2a. This study explored the efficacy, safety, and predictors of treatment response for α-2b plus entecavir among children in a real-world setting. The study included 76 patients aged 3-18 years, all of whom were treated with interferon α-2b plus entecavir. The mean duration of treatment was 401.99 days, and 31.6% (24/76) of patients achieved HBsAg clearance. Competing risk model analyses showed that children with baseline HBsAg <1500 IU/mL (subdistribution hazard ratio [sHR]=2.643, P=0.022) and higher baseline alanine aminotransferase (ALT) level (sHR=1.005, P=0.000) had a higher probability of achieving HBsAg clearance during treatment. Conversely, children with a higher hepatitis B virus loading level (sHR=0.835, P=0.043) and age ≥10 years (sHR=0.243, P=0.002) had a lower probability of achieving HBsAg clearance during treatment. A decrease of >1 log10 in HBsAg level (sHR=3.479, P=0.001) at 12 weeks of treatment was associated with a higher probability of achieving surface antigen clearance. These results indicated that interferon plus entecavir therapy is a promising means of achieving HBsAg clearance in children with CHB. Moreover, HBsAg, ALT, virus loading, and age are indicators of treatment success probability.